Peningkatan kemampuan menemukan ide pokok dalam teks wacana melalui model pembelajaran survey question read recite review pada peserta didik kelas V sekolah dasar - Muhammad Amien Prabowo; Rukayah Rukayah; Fadhil Purnama Adi (Didaktika Dwija Indria, 2019)
The objective of this research to improve students’ ability in finding main idea in a discourse text in fifth grade students’ of elementary school at SD Negeri Pelemrejo, Boyolali 2018/2019 academic year through Survey, Question, Read, Recite, Review (SQ3R) Learning Model. The subjects in this research were a teacher and 17 students. This research was conducted in three cycles. The research data were collected using interview, observation, tests, and document analysis. The data validity was tested by data source triangulation techniques and methodological triangulation technique. The data obtained in this research consisted of quantitative data and qualitative data. The quantitative data were analyzed using descriptive comparative analysis techniques and the qualitative data were analyzed using interactvie models. The first cycle, classical completeness to 41,18%. In the second cycle improvement has increased with classical completeness of 70,59%. The improvement in the third cycle has increased again with classical completeness of 82,35%. Based on the findings as presented above, it can be concluded that the students’ ability in finding main idea in discourse text in fifth grade students’ of elementary school at SD Pelemrejo 2018/2019 academic year can be improved through SQ3R learning models.